Rancang Bangun Sistm Informasi Presensi Praktik Kerja Lapangan (PKL) Berbasis Web dengan Integrasi Geotagging dan Tanda Tangan Digital Menggunakan Framework Next.js - Bagas Saputra; Arsito Ari Kuncoro; Budi Hartono (Jurnal Manajemen Informatika & Teknologi, 2026)
Monitoring the Field Work Practice (PKL) program in vocational high schools often faces challenges regarding attendance data validity due to conventional reporting systems that are vulnerable to location and identity manipulation. This study aims to develop an integrated attendance information system (absensipkl) equipped with layered security based on Multi-Factor Validation. The system was developed using a full-stack web architecture approach with the Next.js framework (App Router) for server performance optimization, and Prisma ORM to ensure relational database integrity. Attendance validation is tightened through Geotagging integration to lock the device's GPS coordinates, combined with a Digital Signature and selfie upload as visual authentication instruments. This applied research was conducted at SMK Ma'arif NU 01 Limpung with 114 12th-grade students majoring in Software Development and Gaming (PPLG) as the subjects. The application has been deployed on a Proxmox virtualization server and fully operated during the internship period from February to April 2026. The implementation results indicate that the system, which contains four main modules (Dashboard, Attendance, Information, Student Data) and is equipped with Role-Based Access Control (Admin, Teacher, Student), is able to effectively eliminate reporting anomalies. In conclusion, the integration of spatial and digital security within the Next.js ecosystem has proven successful in presenting accurate, authentic attendance data and increasing teacher efficiency in evaluating student discipline in real-time